Demographic factors in Swedish adults undergoing root filling and subsequent extraction of a maxillary first molar: a comparative study. (27th February 2018) - Landt, K.; Hagstam‐Harrison, L.; Kvist, T.; Frisk, F.; Dawson, V. S.; Bjørndal, L.; ,; Fransson, H.
Abstract: Aim: To study the demographics of Swedish adults who had received a root filling, followed by extraction during the following 5–6 years in comparison with subjects who had undergone a corresponding root filling with an uneventful outcome. Methodology: The root filled maxillary first molar was chosen as the comparison model. The Swedish Social Insurance Agency provided data on all teeth reported as root filled in Sweden during 2009. A comparison group, equally large as the study group, was constructed by randomly selecting subjects with root filled maxillary first molars, which had not subsequently been extracted, that is, an uneventful outcome. Demographic data on the subjects were obtained from Statistics Sweden: country of birth, disposable income, educational level, age, civil status and gender. Chi‐square, t ‐tests and logistic regression were used for statistical analyses. Results: In the year 2009, 36 139 maxillary first molar teeth were reported to have been root filled, 4362 (12.1%) of which were then recorded as extracted during the following 5–6 year period. Only minor intergroup differences were noted: 86.5% of the study group were Swedish‐born, compared with 84.4% of the comparison group ( P  = 0.007). Women comprised 53.2% of the study group and 50.5% ( P  = 0.01) of the comparison group. There was an association between extractions and gender as well as age; men had a lower odds ratio (OR) for extraction OR, 0.87; confidence interval (CI), 0.80–0.95. For every additional year, the chance for extraction was higher OR, 1.01; CI, 1.01–1.01. No other significant differences were detected. Conclusions: There was only little or no demographic differences between the study group, comprising Swedish adults who had undergone root filling of one of their maxillary first molars in 2009 and subsequent extraction during the following 5–6 years, and the comparison group, with uneventful outcomes after a corresponding root filling.